Towards a global knowledge for environmentally sustainable development agenda in 21 st century southern Africa - Stanford Garikayi Mukasa (Communicare)
After three decades of research and theorizing on the information and communication approach to development, there is no universal consensus among researchers, academics, communication practitioners and development experts on the age-Old question: how does communication and information causally relate to development? What has, instead, emerged is an alphabet soup of theories, concepts, approaches, paradigms and models on how information and communication might impact on development. Whether one looks at the various models of information and communication for development; or whatever one calls it, the theories advanced under the various acronyms still do not conclusively address the basic question raised above. Is there a missing link, variable or factor in all of these attempts to causally relate information and communication to development? What assumptions are embedded in the current theories of information and communication for development? The, article will, by way of addressing these questions, propose an information, communication and knowledge networking strategy that will accommodate in a systematic way the varied and ever-changing information and communication needs of grassroots communities. The paper will map out a strategic vision for the information agenda for southern Africa, with a focus on the development of a new cadre of information agents drawn from a cross section of society, and suggest practical down-ta-earth strategies that can be implemented to successfully. and causally relate information, communication and knowledge to development on a sustained basiS.